Social inclusion and social protection in the EU: interactions between law and policy (Antwerpen, 2012)
"Issues of social inclusion and social protection were brought to the fore of political and academic discussions once again by the Treaty of Lisbon. The fight against social exclusion, the promotion of social justice and protection, as well as social cohesion are confirmed to be among the aims of the Union (Article 3 TEU). Moreover, requirements linked to the guarantee of adequate social protection and the fight against social exclusion should be considered both at the levels of design and implementation of EU policies and activities (Article 9 TFEU).